Morphological characterization of 12 sweet pepper (Capsicum annuum L.) genotypes grown under greenhouse conditions in Costa Rica - Elizondo-Cabalceta, Esteban (2016)
A morphological characterization of 12 sweet pepper genotypes of conical fruit shape grown under greenhouse conditions was conducted, considering both qualitative (five) and quantitative (eight) variables. There were statistically significant differences between genotypes for quantitative variables. Data show a wide variability with respect to plant height (1,26 – 1,71 m), foliar area (100,49 – 158,91 cm2), stem diameter (12,51 – 15,83 mm), stem length (25,75 – 36,88 cm), fruit width (4,97 – 6,19 cm), fruit length (11,24 – 19,43 cm), fruit length/width ratio (1,82 – 3,49), and fruit wall thickness (4,06 – 5,44 mm). This information is useful for growers to choose the best variety for their particular market purposes.